2016
DOI: 10.1016/s0140-6736(16)30379-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical care of incarcerated people with HIV, viral hepatitis, or tuberculosis

Abstract: The burden of HIV/AIDS and other transmissible diseases is higher in prison and jail settings than in the non-incarcerated communities that surround them. In this comprehensive review, we discuss available literature on the topic of clinical management of people infected with HIV, hepatitis B and C viruses, and tuberculosis in incarcerated settings in addition to co-occurrence of one or more of these infections. Methods such as screening practices and provision of treatment during detainment periods are review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 83 publications
0
85
0
2
Order By: Relevance
“…As reported elsewhere, opt-out HIV screening seemed an efficient strategy to diagnose HIV among inmates [7,27,28]. It allowed diagnosing a high number of early stage infections, with no physical signs of immune depression (nearly 80% were CDC-stage A).…”
Section: Discussionmentioning
confidence: 83%
“…As reported elsewhere, opt-out HIV screening seemed an efficient strategy to diagnose HIV among inmates [7,27,28]. It allowed diagnosing a high number of early stage infections, with no physical signs of immune depression (nearly 80% were CDC-stage A).…”
Section: Discussionmentioning
confidence: 83%
“…International surveys have shown that a small portion of the world imprisoned population has consistent access to measures for prevention of STIs, highlighting the low frequency of condom use in the prison environment, which, among other factors, has the existence of imposed sexual relations as determinant. (26,27) Condom use is an important measure for the prevention of new cases of hepatitis B, because its efficacy is proven as a physical barrier in the transmission of particles with size similar to that of small STI-causing viruses. In addition, if used correctly, it reduces the risks of slides or ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Time during incarceration and immediately after release back to the general community has also been implicated in transmission of HBV infection. Prisons are a potential location for treatment of chronic illness, including chronic HBV infection [4, 5]. However, during our review of the literature, we found no descriptions of treatment of active hepatitis B infection in prisoners.…”
Section: Introductionmentioning
confidence: 93%